Interrelation of National Security and Strategy of the State Development of Russia - Andrey Andreevich Kovalev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article, the attempt to designate the most priority directions forming effective system of national security of the state is made. The geopolitical and economic elements of the system of national security of the state are considered and analyzed.